Public policy ethics in the relocation of the national capital analysis of social, economic, and environmental issues - Fadilah, Ulvia; Ramdani, F. Ajeng (Institute Of computer Science (IOCS), 2025)
The relocation of Indonesia's national capital is a strategic policy aimed at promoting equitable development and reducing pressure on Jakarta as the center of government and economy. However, this policy raises a number of ethical problems related to its impact on social, economic and environmental aspects. This study aims to analyze the relocation policy from the perspective of public policy ethics, focusing on social challenges such as the rights of local communities, economic welfare, and environmental sustainability. A qualitative approach is used in this study with literature analysis methods and interviews with public policy experts, practitioners, and community representatives in East Kalimantan. The results show that while the relocation of IKN has the potential to provide national economic benefits, there are significant ethical issues that include the risk of marginalization of local communities, threats to forest ecosystems, and sustainable resource management. The study highlights the need for transparency, more inclusive public participation, and the application of environmental justice principles in the planning and implementation of IKN policies. In conclusion, to ensure legitimacy and community support, IKN's transfer policy must consider ethical principles of public policy that prioritize the balance between national interests and the rights of local communities and environmental sustainability.